MARINE OPTICAL PROPERTIES OF SEAWATER IN NHA TRANG BAY - Thu, Phan Minh; Long, Bui Hong; Lang, Pham Ngoc (Vietnam Journal of Marine Science and Technology, 2017)
Marine optics of seawater includes apparent optical properties (AOP) and inherent optical properties (IOP). Based on survey data in the period of 2013-2014, the paper showed features and spatial and temporal variations of marine optical properties of seawater as well as the impacts of some environmental parameters on these variables. The average of light attenuation coefficient was quantitation of 0.122 ± 0.052 m-1 in the dry season and 0.187 ± 0.121 m-1 in the rainy season. Euphotic zone depth, z1% reflecting the depth where photosynthetically available radiation (PAR) is 1% of its surface value, averaged 29.50 ± 9.05 m in the dry season and 24.68 ± 10.60 m in the rainy season. The absorption coefficient of detritus components in water virtually underwent few changes between dry and rainy seasons but CDOM (Colored Dissolved Organic Matter) in the rainy season was much higher than that in the dry season. The seawater optical properties were influenced by the seawater components and closely related to environmental parameters of waters.